2017
DOI: 10.20517/2572-8180.2017.01
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, awareness, and practice of forensic odontology among dental surgeons in Bhubaneswar, India

Abstract: How to cite this article: Rahman J, Routray S, Mishra SS, Mohanty I, Mohanty N, Sukla N. Knowledge, awareness, and practice of forensic odontology among dental surgeons in Bhubaneswar, India. J Unexplored Med Data 2017;2:26-33. Aim:The aim of the study was to evaluate knowledge, awareness, and practice related to forensic odontology among dental surgeons in Bhubaneswar, East India. Methods: A blind cross-sectional study, using a questionnaire with close-ended questions, was carried out. Interns were included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…In addition, this finding broadly supports the work of other studies in this area linking dental specialty and knowledge of forensic odontology which highlighted that undergraduate student are well informed about the new branch of deontology. Additionally, knowledge about bite marks was found to be adequate among postgraduates than the undergraduates in the present study, which is similar to studies by [11]. Other studies revealed that the knowledge about bite marks was not known to 18% of the dental practitioners [12].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, this finding broadly supports the work of other studies in this area linking dental specialty and knowledge of forensic odontology which highlighted that undergraduate student are well informed about the new branch of deontology. Additionally, knowledge about bite marks was found to be adequate among postgraduates than the undergraduates in the present study, which is similar to studies by [11]. Other studies revealed that the knowledge about bite marks was not known to 18% of the dental practitioners [12].…”
Section: Discussionsupporting
confidence: 87%
“…[9] Another study conducted by Rahman J et al among among dental surgeons in Bhubaneswar, East India also observed that there is adequate level of knowledge and awareness regarding forensic odontology in all the groups investigated. [10] Poor knowledge has been reported in another study conducted by Alshaqaq et al outside the India in Riyadh city of Saudi Arabia. [11] This could be owing to multiple reasons.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the awareness of lip prints in the identification of an individual, 85.3% of the present study participants, and bite marks being an important tool in assessing a crime scene there was awareness of 89.2% of the study participants, likewise, were aware of it. 77.5% of the participants in a study conducted by Rahman et al 12 in 2017 and 42% of the participants in the study conducted by Naik et al 17 in 2018 were aware of the use of lip prints in forensic odontology. Similar to the results of our study, 90.2% of the Rahman et al 12 study participants were aware of that bite marks are an essential tool in assessing a crime scene but on contrary, only 57% of the participants in the Naik et al 17 study was aware of it.…”
Section: Discussionmentioning
confidence: 98%